Increase in the 64-kDa subunit of the polyadenylation/cleavage stimulatory factor during the G(0) to S phase transition - Martincic, Kathleen (The National Academy of Sciences, 1998)
The amount of the 64-kDa subunit of polyadenylation/cleavage stimulatory factor (CstF-64) increases 5-fold during the G(0) to S phase transition and concomitant proliferation induced by serum in 3T6 fibroblasts. Higher levels of CstF-64 result in an increase in CstF trimer. The rise in CstF-64 occurs at a time when the amount of poly(A)-containing RNA rose at least 5–8 fold in the cytoplasm. Primary human splenic B cells, resting in G(0), show a similar 5-fold increase in CstF-64 when cultured under conditions inducing proliferation (CD40 ligand exposure). Therefore, the increase in CstF-64 is associated with the G(0) to S phase transition. As B cell development progresses, RNA processing changes occur at the Ig heavy chain locus resulting in a switch from the membrane- to the upstream secretory-specific poly(A) site. Treating resting B cells with agents triggering this switch in Ig mRNA production along with proliferation (CD40 ligand plus lymphokines or Stapylococcus aureus protein A) induces no further increase in CstF-64 above that seen for proliferation alone. The rise in CstF-64 is therefore insufficient to induce secretion. After stimulation of a continuously growing B cell line with lymphokines, a switch to Ig μ secretory mRNA and protein occurs but without a change in the CstF-64 level. Therefore, an increase in CstF-64 levels is not necessary to mediate the differentiation-induced switch to secreted forms of Ig-μ heavy chain. Because augmentation of CstF-64 levels is neither necessary nor sufficient for Ig secretory mRNA production, we conclude that other lymphokine-induced factors play a role.